Psychological Messages in the Linguistic Landscape of Humbang Hasundutan Regency Tourist Destinations: Tourists' Perspectives - Selli; Robert Sibarani; Rujiman; Morida Siagian (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to explore the psychological messages contained in the linguistic landscape of tourist destinations of Humbang Hasundutan Regency, seen from the perspective of tourists. Tourist destinations play an important role in creating unique and enthralling experiences for tourists. This research method involved in-depth interviews with several tourists who had visited Humbang Hasundutan Regency. The collected data were analyzed using a qualitative approach, focusing on identifying emerging themes related to psychological messages in the linguistic landscape. The results showed that the linguistic landscape of Humbang Hasundutan Regency communicated diverse psychological messages. Tourists express that the use of local languages, cultural symbols, and local stories in destination signs, banners, and brochures provides a sense of authenticity and cultural richness that influences their perception of the place. In addition, the use of persuasive and descriptive language in tourist descriptions and interactions with locals also exerts a significant influence on the emotional mood of tourists.